Caramel colour and process contaminants in foods and beverages: Part II – Occurrence data and exposure assessment of 2-acetyl-4-(1, 2, 3, 4-tetrahydroxybutyl)imidazole (THI) and 4-methylimidazole (4-MEI) in Belgium. (30th July 2018) - Fierens, T.; Van Holderbeke, M.; Cornelis, C.; Jacobs, G.; Sioen, I.; De Maeyer, M.; Vinkx, C.; Vanermen, G.
Highlights: THI and 4-MEI were analysed in more than 500 food products. Food levels up to 551 µg/kg for THI and 2, 835 µg/kg for 4-MEI were found. Average intake amounted to 0.02–0.36 (THI) and 0.4–3.7 µg kg −1  bw −1  day (4-MEI). Coffee, cola and beer are main contributors to dietary THI and 4-MEI intake in Belgium. Abstract: In Europe, 2-acetyl-4-(1, 2, 3, 4-tetrahydroxybutyl)imidazole (THI) and 4-methylimidazole (4-MEI) are – to a certain level – allowed to be present in the food colours ammonia caramel (E 150c) and sulphite ammonia caramel (E 150d). Besides their presence in food colours, exposure to these contaminants may also include other dietary sources. This study describes the occurrence of THI and 4-MEI in a wide variety of food products (n = 522) purchased from the Belgian market and their dietary intake in Belgian consumers from 15 years old onwards. THI was found to be present in 22.4% of the investigated foods at a level up to 551 µg/kg. For 4-MEI (57.7% quantifiable), concentrations up to 2, 835 µg/kg were observed. The average dietary intake amounted to 0.02–0.36 µg kg −1  bw −1  day for THI and 0.4–3.7 µg kg −1  bw −1  day for 4-MEI. Coffee, cola and beer were contributing most to the dietary THI and 4-MEI intake in Belgium.